Kepemimpinan: Sebuah Kajian Literatur - Juhji Juhji (At-Tarbiyat, 2020)
This study aims to explain the understanding of management, scope of management, and leadership of Islamic education. Library studies are used as a method of research. The data is retrieved, collected, and analyzed from scientific books and journals that have similar topics, then used as writings and summations. The results showed that management activities cover a broad spectrum, ranging from activities to determining the direction of the organization in the future, creating organizational activities, encouraging cooperation between fellow members of the organization, and overseeing activities in achieving the goals. Islamic education leadership is a leadership process in Islamic education to move, influence, motivate, and direct people within educational institutions to achieve the goals that have been formulated.